2020
DOI: 10.1589/jpts.32.489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flexi bar training model to health-related physical fitness in overweight adults

Abstract: The purpose of this study was to assess the effects of flexi bar training model and moderate running exercise on health-related physical fitness in overweight adults. [Participants and Methods] Forty participants were randomly assigned to an experimental (20 participant performing flexi bar training model (FBT)) and control (20 participant performing moderate running exercise (MRE) group. The participant in both groups then underwent program training 50 min/day, 3 times a week, for 12 weeks. The main outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[13][14][15][16] Flexi-bar is a type of vibration device, and it consists of a bar, with two weighty rubbers at each end of the bar. 17 Some studies have reported that long-term flexi-bar training has positive effects on the muscle mass, 18 19 muscle strength 20 and physical performance. 21 22 A study reported that the thickness of the transversus abdominis muscle of young university adults increases to 2.4 mm after a 6-month (48 times) flexi-bar training programme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Flexi-bar is a type of vibration device, and it consists of a bar, with two weighty rubbers at each end of the bar. 17 Some studies have reported that long-term flexi-bar training has positive effects on the muscle mass, 18 19 muscle strength 20 and physical performance. 21 22 A study reported that the thickness of the transversus abdominis muscle of young university adults increases to 2.4 mm after a 6-month (48 times) flexi-bar training programme.…”
Section: Introductionmentioning
confidence: 99%
“…18 In another study, the overweight adults with a 12-week flexi-bar training programme exhibited a significant increase in handgrip strength, which was significantly different from that of the control group. 20 In a study on the physical performance by Lee and Han, older people with chronic stroke exhibited significant improvement in the score of Berg Balance Scale, the duration of completion of timed-up-and-go test (TUG) and 10-metre walking test (10MWT) after 4 weeks of flexi-bar training (20 times). 21 Moreover, the flexi-bar training could induce a strong stimulus on the muscle during submaximal exercise, 17 23 Strengths and limitations of this study ► This study is the first parallel randomised controlled trial on the effects of a 12-week flexi-bar training programme on muscle strength and physical function in older people with dynapenia, and the study design involves a placebo group.…”
Section: Introductionmentioning
confidence: 99%